Adding green and black teas in a rice straw-based sheep diet improves in vitro dry matter degradability without affecting gas production and pH - Ramdani, Diky; Chaudhry, Abdul Shakoor (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Rice straw (RS) is widely available in South East Asia and it can be used as a source of fibres for ruminant animals. However, RS has poor palatability and nutritional values. Thus, the use of concentrate (CON) as a dietary supplement is required to increase the utilisation of RS. Green (GT) and black (BT) teas can act as natural dietary additives in a CON. This study evaluated nutrient compositions of the diet ingredients and the impact of supplementing GT and BT in a rice straw-based sheep diet on in vitro dry matter degradability (IVDMD), total gas production (TGP) and pH during more than 24 hours of incubations. The CON, GT, and BT had higher crude protein, organic matter, and metabolizable energy but lower fibre fractions than RS. The GT and BT had greater total tannins than CON and RS confirming that they could potentially be used as natural dietary additives. In addition, GT supplementation improved IVDMD without affecting TGP and pH values. Conversely, BT supplementation did not improved IVDMD. Thus, BT is less preferable as a ruminant dietary supplement than GT.